Ethical Principles in Public Health Research: Contextual Understanding with Islamic Legal Principles - Faradilla Diwanta; Irwansyah Irwansyah; Faiqah Adnin Purba (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
This research explores the role and significance of ethical principles in the context of societal research, with particular emphasis on Islamic legal perspectives. Through contextual analysis, this research identifies relevant ethical principles and applies the Islamic legal framework as a moral foundation. The problem was motivated by cases of ethical lapses in health research. Not only does this happen in foreign countries, but in Indonesia, there are also frequent ethical lapses in health research. An important event that opened the eyes of the whole world and embarrassed the scientific community was the Doctor's Trial, which was carried out in the city of Nuremberg, Germany, after the end of World War II. The Doctor's Trial was a series of trials held after World War II to try individual Nazis for war crimes and crimes against humanity. The Doctor's Trial specifically highlights the medical crimes committed by Nazi doctors. Apart from that, there were also irregularities that occurred at Tuskegee, namely that medication was not given to participants after the research was carried out, resulting in seven people dying and 150 people suffering from heart failure. Not only that, the problem of violations of research ethics also occurred in Indonesia, namely research on the drug "Nerve Pill," which involved a hospital in Jakarta. Health research, as a scientific method, is regulated by Islamic law, which includes rules from Allah's revelation and the Prophet's sunnah and is in accordance with the application of applicable Islamic legal principles so that there is no deviation from Islamic religious values. This article aims to discuss the problem of deviations from Islamic law in the context of health research by highlighting practices or policies that may not be in line with the principles of Islamic law in the health aspect. The research method uses a literature study, focuses on relevant literature, and identifies knowledge gaps. In the discussion, the principles of Islamic law, such as monotheism, justice, and equality, were identified as the ethical foundations of health research. Although there is no direct Islamic law governing health research ethics, these principles can serve as guidelines for carrying out research ethics according to Islamic values. In conclusion, the principles of Islamic law can guide researchers' behavior, ensure research is conducted with respect for Islamic values, and prevent ethical deviations. In this way, health research can provide benefits that suit society's needs.